PENGARUH EMPATI DAN RELIGIUSITAS TERHADAP KEPATUHAN BERZAKAT PEGAWAI ( STUDI PADA BADAN ZAKAT NASIONAL KABUPATEN TEBO ) - Aysah putri mahardika; A.A. miftah; Erwin saputra siregar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of this research is to find out (1) whether empathy has a significant effect on zakat compliance of Muslim employees who distribute zakat to Basnaz, Tebo Regency, (2) whether religiosity has a significant effect on zakat compliance among Muslim employees. Tebo Regency and (3) whether empathy and religiosity simultaneously influence Muslim employees' zakat compliance with Muslim employees who distribute zakat to Basnaz in Tebo Regency. This research uses quantitative research methods with descriptive research type. The data sources in this research are Muslim employees who distribute zakat to Basnaz, Tebo Regency. The data collection methods that researchers use are questionnaires, documentation and observation. The analytical method used in processing the data is multiple linear regression analysis, using the SPSS (Statistical Packade For Social Science) application. Based on the results of the research and discussion carried out in the previous chapter, the conclusions were drawn: (1) Empathy has a significant effect on zakat compliance among Muslim employees who distribute zakat to Basnaz, Tebo Regency, (2) Religiosity has a significant effect on zakat compliance among Muslim employees who distribute zakat to Basnaz Regency. Tebo and (3) Empathy and religiosity simultaneously have a significant effect on compliance with zakat among Muslim employees who distribute zakat to Basnaz, Tebo Regency.